Pumpkin and Pastel Wine, A Fruit and A Legume Of The Cucurbitaceous Family in Green Circular Economy With Zero Waste - Robijaona Rahelivololoniaina Baholy; Letsara Rokiman; Herimanantena Miarantsoa Tinah; Razafindrakoto Fanoina Ny Riana; Rabeharitsara Andry Tahina; Razafimahefa Mirana Verohanitra; Koto-Te-Nyiwa Ngbolua; Rakotomamonjy Pierre (Britain International for Academic Research (BIAR) Publisher, 2024)
This study explores the viability of watermelon (Citrullus lanatus) and pumpkin (Cucurbita pepo subsp. Pepo) as unconventional sources for sustainable winemaking, contributing to a zero-waste circular economy in viticulture. The research employs a multidimensional methodology encompassing chemical analyses, sensory evaluations, and environmental impact assessments to scrutinize the entire lifecycle of wine production. The findings reveal watermelon wine's superiority, boasting a 14° alcohol content, while pumpkin wine ranges at 11°. Both wines maintain physico-chemical and organoleptic attributes, with minimal alterations in micronutrient content. The compost generated from processing waste contains essential nutrients for plant growth. Comparative analysis underscores the advantageous nature of this compost, laying the foundation for sustainable winemaking practices in Madagascar and illuminating the untapped potential of tropical fruits in the global viticultural landscape. This study, pioneering the valorization of unconventional fruit and vegetable in Madagascar, strives to contribute to the discourse on environmentally conscious winemaking, fostering a paradigm shift toward ecologically harmonious practices in the agro-industrial sector.